Head injury in mixed martial arts: a review of epidemiology, affected brain structures and risks of cognitive decline. Issue 4 (2nd October 2021) - Schlegel, Petr; Novotny, Michal; Valis, Martin; Klimova, Blanka
ABSTRACT: Background: The popularity trend of mixed martial arts (MMA) is steeply increasing, especially in the very young population. Unfortunately, MMA carries an enormous risk of head trauma. Purpose: The aim of this article is to provide review of studies on the association between head injuries and cognitive functions in MMA fighters. Methods: A systematic literature review was performed. Web of Science, PubMed, Springer, and Scopus databases were used. A total of 30 studies were identified. The inclusion criteria were as follows: studies with MMA fighters and head injuries and/or TKO/KO and/or reduction of cognitive functions in these fighters. Results: The results indicate that the incidence of head traumas ranges between 58% and 78% of all injuries. The King-Devick test seems to be a suitable rapid tool used in the studies to assess the extent of cognitive impairment. Among the detected studies, the post-fighting scores were significantly worse for fighters with head trauma during the match. We also found anomalies in MMA fighters in different brain structures, but it seems that the thalamus and caudate are the most affected. The impaired performance in processing speed, verbal memory and psychomotor speed is regularly confirmed in studies with MMA fighters. In addition, head traumatization seems to be a risk factor for the development of neurodegenerative disorders and it may be one of the possible causes of chronic traumatic encephalopathy (CTE). Several global medical societies have identified MMA as a violent and dangerous sport and have called for its ban – but unsuccessfully. Conclusion: Therefore, possible recommendations should include increased medical supervision of the fighter (during his career, but also after it) and the introduction of practical safety instructions for fighters to reduce the risk of developing CTE. With the increasing popularity of MMA, the risk of CTE should not be underestimated.